POLA KOMUNIKASI INTERPERSONAL ORANG TUA DALAM MEMBENTUK KEPRIBADIAN ANAK - Anton Widodo; Hemlan Elhany; Dimas Yoga Pangestu; Andi Rahmad (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
Communication in the family is the key to be effective in educating children and for the process of social and emotional development in children, the purpose of this study is to find out how the efforts of parental communication patterns in shaping children's personalities in Skrikaton Village, Buay Madang Timur District, East OKU Regency, the research method used is descriptive quantitative research method, Based on the results of parents' interpersonal communication research in shaping children's personalities in Srikaton Village, there are 3 Communication Patterns applied in the families of each informant, namely Family Communication with Laissez-faire patterns, Family Communication with Pluralistic patterns and Family Communication with Protective patterns , The application of each pattern of communication in the family has a negative and positive impact, can affect the development of children who tend to be directed and supervised by both parents so that the cultivation of akhlaq from an early age is obtained and becomes a provision for children to socialize in community life can uphold the dignity of parents and maintain the good name of the family.